Effect of Advertising, Sales Promotion, Publicity and Personal Selling on Customer’s Saving Decisions : Case Study at Baitul Maal Wa Tamwil UGT Nusantara Sub-Branch Muncar, Banyuwangi - Abdul Rouf; Zuni Fitrowati; Indah Yuliana (Iqtishodia: Jurnal Ekonomi Syariah, 2021)
Promotion Mix is the maximum effective device to draw and keep customers. This study aims to analyze the impact of advertising, sales promotion, publicity, and personal selling on customer decisions to save at BMT UGT Nusantara Sub-Branch Muncar Banyuwangi. This study  was quantitative, the sample used was 100 customers. Data series strategies on this examine are questionnaires and documentation. Data evaluation the usage of validity take a look at, normality take a look at, classical assumption take a look at, and more than one linear evaluation take a look at the usage of SPSS 25. This study conclude that an effects of Advertising (X1), Sales Promotion (X2), Publicity (X3), and Personal Selling (X4) was significant and positif impact concurrently on customer’s saving decisions, while private promoting variable has in significant impact on on customer’s saving decisions.